KCC2-dependent Steady-state Intracellular Chloride Concentration and pH in Cortical Layer 2/3 Neurons of Anesthetized and Awake Mice - Boffi, Juan C.; Knabbe, Johannes; Kaiser, Michaela; Kuner, Thomas (Frontiers in Cellular Neuroscience, 2018)
Neuronal intracellular Cl- concentration ([Cl-]i) influences a wide range of processes such as neuronal inhibition, membrane potential dynamics, intracellular pH (pHi) or cell volume. Up to date, neuronal [Cl-]i has predominantly been studied in model systems of reduced complexity. Here, we implemented the genetically encoded ratiometric Cl- indicator Superclomeleon (SCLM) to estimate the steady-state [Cl-]i in cortical neurons from anesthetized and awake mice using 2-photon microscopy. Additionally, we implemented superecliptic pHluorin as a ratiometric sensor to estimate the intracellular steady-state pH (pHi) of mouse cortical neurons in vivo. We estimated an average resting [Cl-]i of 6 ± 2 mM with no evidence of subcellular gradients in the proximal somato-dendritic domain and an average somatic pHi of 7.1 ± 0.2. Neither [Cl-]i nor pHi were affected by isoflurane anesthesia. We deleted the cation-Cl- co-transporter KCC2 in single identified neurons of adult mice and found an increase of [Cl-]i to approximately 26 ± 8 mM, demonstrating that under in vivo conditions KCC2 produces low [Cl-]i in adult mouse neurons. In summary, neurons of the brain of awake adult mice exhibit a low and evenly distributed [Cl-]i in the proximal somato-dendritic compartment that is independent of anesthesia and requires KCC2 expression for its maintenance.